2022
DOI: 10.21203/rs.3.rs-2307446/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers to telemedicine establishment and development in Iran:  a systematic review

Abstract: Background: Despite the rapid growth of telemedicine technology in the health system in developed and high-income countries and the undeniable benefits of this technology, its establishment and development in developing countries, including Iran, faces many barriers. Telemedicine has not been deployed in delivering routine healthcare services in Iran's health system. In this regard, precise identification of challenges and barriers to telemedicine implementation and development is necessary. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In other technologies including telehealth, healthcare professionals were less often the main users of applications. The reasons can be the lack of familiarity of healthcare professionals with technologies and the lack of cultural fit or motivation to use new tools [117]. Healthcare professionals resist the use of Telehealth which may be due to a sense of threat from this technology, reduced autonomy, and indirect costs associated with it [5].…”
Section: Rq4: Users Of Digital Health Technologymentioning
confidence: 99%
“…In other technologies including telehealth, healthcare professionals were less often the main users of applications. The reasons can be the lack of familiarity of healthcare professionals with technologies and the lack of cultural fit or motivation to use new tools [117]. Healthcare professionals resist the use of Telehealth which may be due to a sense of threat from this technology, reduced autonomy, and indirect costs associated with it [5].…”
Section: Rq4: Users Of Digital Health Technologymentioning
confidence: 99%
“…In their study, the most significant barriers were related to the building block of governance/leadership, which was an integral part of other building blocks of the health system in any country. The authors concluded that establishment and development of telemedicine technology in Iran, ensuring the existence of strategic policy frameworks coupled with some other factors such as effective supervision, coalition building, rules and regulations, inter- and intra-sectoral collaboration and community engagement, were necessary (Mehrolhassani et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%